Analisis Pertanggungjawaban Pidana terhadap Pelaku Penyebaran Data Pribadi melalui Media Sosial - okta ria (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The rapid growth of social media has increased the risk of unauthorized dissemination of personal data. This normative legal research aims to examine the legal framework governing personal data protection, criminal liability for the unauthorized disclosure of personal data, and the enforcement of relevant laws in Indonesia. The findings indicate that personal data protection is regulated under the Personal Data Protection Law, the Electronic Information and Transactions Law, and the Criminal Code. These three legal instruments provide legal certainty, with the Personal Data Protection Law serving as the primary legal basis (lex specialis) for resolving personal data breach cases. It is recommended to strengthen digital literacy, enhance law enforcement capacity, and establish integrated guidelines for handling personal data breach cases.